Hubungan Antara Iklim dan Budaya Madrasah dengan Motivasi Kerja Guru pada Madrasah Tsanawiyah di Kecamatan Sinjai Barat Kabupaten Sinjai - Danial, Danial; Damopolii, Muljono; Syamsudduha, Syamsudduha (Universitas Muhammadiyah Surakarta, 2019)
The purpose of this study is to analyze and examine the correlation between madrasah climate and culture, and teachers? work motivation at Madrasah Tsanawiyah in West Sinjai District of Sinjai Regency. This research uses a correlational study with quantitative approach. The participants of this research are 64 teachers from Madrasah Tsanawiyah in West Sinjai District. Data collection technique with questionnaires and then analyzed by using product moment correlation for partial testing and multiple correlation for simultaneous testing. The research reveals some significant findings. First, the finding indicates a positive correlation between madrasah climate and teachers? work motivation by correlation coefficient value at 0,448 (which is at moderate level correlation). Second, the finding indicates a positive correlation between madrasah culture and teachers? work motivation by correlation coefficient value at 0,559 (which is at moderate level correlation). Third, the finding indicates a positive correlation between madrasah clime and culture, and teachers? work motivation by correlation coefficient value at 0,572 (which is at moderate level correlation).